2015
DOI: 10.1186/s12880-015-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined PET/CT-perfusion in patients with head and neck cancers might predict failure after radio-chemotherapy: a proof of concept study

Abstract: Background[18F]FDG-PET/CT imaging is broadly used in head and neck cancer (HNSCC) patients. CT perfusion (CTP) is known to provide information about angiogenesis and blood-flow characteristics in tumors. The aim of this study was to evaluate the potential relationship of FDG-parameters and CTP-parameters in HNSCC preand post-therapy and the potential prognostic value of a combined PET/CT with CTP.MethodsThirteen patients with histologic proven HNSCC were prospectively included. All patients underwent a combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Multi-parametric imaging with functional imaging techniques has recently been used to evaluate biological properties of malignant tumours as changes at a cellular level typically occur prior to morphological changes. CT perfusion (CTP) has already been reported to provide a valuable information on tumour vascularity 8, 9, 10. In recent years, diffusion-weighted (DW) MR imaging (MRI) and dynamic contrast-enhanced MRI (DCE) have been used for assessing tumour biology and to predict tumour response and survival rates in patients with HNSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-parametric imaging with functional imaging techniques has recently been used to evaluate biological properties of malignant tumours as changes at a cellular level typically occur prior to morphological changes. CT perfusion (CTP) has already been reported to provide a valuable information on tumour vascularity 8, 9, 10. In recent years, diffusion-weighted (DW) MR imaging (MRI) and dynamic contrast-enhanced MRI (DCE) have been used for assessing tumour biology and to predict tumour response and survival rates in patients with HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…CT perfusion (CTP) has already been reported to provide a valuable information on tumour vascularity. 8 , 9 , 10 In recent years, diffusion-weighted (DW) MR imaging (MRI) and dynamic contrast-enhanced MRI (DCE) have been used for assessing tumour biology and to predict tumour response and survival rates in patients with HNSCC. DWI is a widely used technique that allows for non-invasive measurement of the Brownian motion of water molecules by calculating the apparent diffusion coefficient (ADC) which reflects tumour cellularity and tissue microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Results of similar studies in human patients with head and neck cancer are inconsistent, yet most studies have found that high pre-treatment BF and BV were associated with a better response to treatment, locoregional control, or survival. 20,[33][34][35][36][37][38] This could be explained by the fact that well vascularized and well oxygenated tumors are generally better responders to RT. 39 In the current study, 3 out of 4 dogs who showed a reduction in size of the tumor during RT also showed an increased in BF and BV at 12 Gy.…”
Section: Discussionmentioning
confidence: 99%